Understanding university students’ fast food consumption behavior and associated health concern - Chowdhury, Md. Ridowan; Rahman, Md. Maruf (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.